Blast Protection of Buildings. - Engineers, American Society of Civil (Standards Series, 2023)
Standard ASCE/SEI 59-22 provides minimum requirements for planning, design, construction, and assessment of new and existing buildings subject to the effects of accidental or malicious explosions.